RESEARCH ON 3D OBJECT SURFACE SIMULATION TECHNIQUES AND VIRTUAL REALITY APPLICATIONS IN TEACHING - Nguyen Thi Quyen (Tạp chí Khoa học)
Virtual reality (VR) technology is now widely applied in various fields such as education, military, and medicine. Particularly in medical education, the application of VR in simulating human body parts enhances visualization, increases interactivity, and improves teaching effectiveness. This approach helps students easily visualize and quickly grasp theoretical concepts and fosters engagement in learning. This paper presents two fundamental techniques for simulating the respiratory system: simulation modelling and rendering techniques in a virtual reality environment. The author has researched and developed a simulation model based on the continuously oriented polygonal modelling method. Experimental results demonstrate the ability to recreate the external structure of the respiratory system in a 3D model and effectively interact with the respiratory system in a virtual environment. These findings confirm the potential of VR technology in supporting teaching and medical research.